Selection of Voltage Referential from the Power Quality and Apparent Power Points of View - Paredes, Helmo K. Morales; Deckmann, Sigmar M.; Silva, Luis C. Pereira da; Marafão, Fernando P. (IntechOpen, 2011)
None